Learning through teaching: Teaching the nature of scientific inquiry in online outdoor learning environments - ERDAŞ KARTAL, Eda; MESCİ, Günkut (International Journal of Assessment Tools in Education, 2022)
This study aims to examine the developments of 50 pre-service teachers' NOSI views during a 14-week implementation in the online outdoor learning environment. This is an experimental study that examines each participant's views and changes about NOSI using an open-ended questionnaire (VASI), and follow-up interviews. The data were analyzed by using content analysis. Almost all participants positively improved their views through the explicit/reflective approach and teachers' own experiences by practicing. In this study, the views of pre-service teachers developed more clearly after preparing lesson plans and their teaching practices. This is an indication that NOSI teaching, which does not provide the experience of conveying their learning outcomes to their practices to the participants is limited on its own and that the importance of “learning through teaching” in teachers' in-service and pre-service training on this subject should not be overlooked. Online teacher education in outdoor learning environments might be used in the development of NOSI views of pre-service teachers. We think that it is important to investigate the effect of this training on teacher education. These types of training might create a more economical and sustainable alternative for the development of NOSI views of wider groups of pre-service and in-service teachers.
Keywords: Nature of scientific inquiry; Outdoor learning; Teacher training; Learning through teaching; Alan Eğitimleri; learning through teaching; nature of scientific inquiry; teacher training; L; Other Fields of Education; Education; Nature of scientific inquiry; Outdoor learning; Teacher training; Learning through teaching; Nature of scientific inquiry; Outdoor learning; Teacher training; Learning through teaching; outdoor learning; 4. Education; 16. Peace & justice